Parameter-Driven Campbell Diagram Variations in Turbocharger Rotors: A Rotordynamic Simulation Study Using ROSS - Márk Pesthy; Máté Boros; Csaba Tóth-Nagy (Engineering Proceedings)
This study investigates the influence of rotor design parameters on the Campbell diagrams of automotive turbocharger rotors using rotordynamic simulations. A finite element model of the rotor is developed within the Python-based ROSS package, incorporating key parameters such as disk mass, lubricant viscosity, and bearing positioning. Employing this model, simulations are conducted to generate Campbell diagrams across a range of operational speeds. The analysis focuses on how variations in these parameters affect the critical speeds and corresponding vibration modes identified in the Campbell diagrams. The results provide valuable insights into the rotordynamic behavior of automotive turbochargers and their sensitivity to design choices. This information can be utilized to optimize rotor design for improved stability, reduced noise generation, and enhanced overall performance.